Gender Differences in Second Language Speech Production and Communicative Strategies (Journal of Natural Language and Linguistics, 2025)
Using conversational analysis to study gender differences in the second language speech production and communicative strategies of selected grade 8 students of Baco National High School, specifically recognizing the differences in terms of the amount of talk, turn-taking system, and conversational elements, this study employed single-sex and mixed-sex conversations which only comprised of 3 males and 3 females purposively selected from Grade 8 curriculum level. The researcher transcribed the recorded conversations verbatim before adapting them to the Jeffersonian Transcription system. The study revealed that women are inarguably more verbose than men and that men interrupt and overlap more than men in mixed-sex conversations, while women overlap with the same sex more frequently, resulting in non-completion of turns. Moreover, it has also been found that men proclaim their dominance by using conversational strategies such as interrupting and overlapping, while women tend to talk more to ascend in mixed-sex conversations. On the other hand, both sexes tend to be more comfortable in expressing themselves when conversing with the same sex; however, men are more inclined to use non-verbal language with the same sex to comprehend each other. Finally, it was discovered that men’s conversational styles are more likely to question, instruct, correct, disagree, and switch codes, while women tend to execute conforming, informing, repairing, and hedging.